Study on The Ageing Performance on Kenaf Insulating Presspaper with Natural Ester - Nurul 'Izzati, Hashim; Mohd Taufiq, Ishak; Nurizah Insyirah, Md Noh; Ja'afar, Adnan; Mohd Solehin, Mohd Nasir; Siti Aminah, Mohd Noor (2021)
This study aims to evaluate the ageing performance of Kraft and Kenaf insulation press-paper in Natural Ester (NE), which could be applied in a power transformer. Kenaf fiber was produced by Kraft pulping process is considered as potential insulation press-paper due to higher cellulose. Due to environmental concerns, NE uses have been considered an alternative to mineral oil. In this experiment, an accelerated ageing test was carried out with transformer insulation press-paper. Kraft and Kenaf press-paper were impregnated in NE with a copper strip of 90℃ and 140℃ for 10,20 30 days. Fourier transform infrared spectroscopy (FTIR) result showed that O-H's absorption intensity decreased, while C-H, C=O, and C-O bond increased with the ageing time. The viscosity measurements have been used to compare the stability of aged NE with Kraft and Kenaf press-paper at different ageing time. It is found that the viscosity results showed aged NE with Kraft press-paper is higher than Kenaf presspaper as the duration of ageing increase.